0581 Sleep Patterns and "OFF"-Time in Patients with Parkinson's Disease and Motor Fluctuations. (25th May 2022) - Hauser, Robert; Videnovic, Aleksandar; Soares-da-Silva, Patrício; Liang, Grace; Olson, Kurt; Jen, Eric; Rocha, José-Francisco; Klepitskaya, Olga
Abstract: Introduction: Sleep disruptions in patients with Parkinson's disease (PD) include difficulty falling/staying asleep, which can contribute to daytime sleepiness and overall worsening of health, mood, and quality of life. Although sleep disturbances in PD are multifactorial, nighttime motor symptoms can negatively affect sleep. To better understand how "OFF"-episodes affect sleep, post-hoc analyses were conducted using baseline data from two phase 3 studies of opicapone, an approved once-daily adjunctive treatment to levodopa/carbidopa (LD/CD) in patients with PD experiencing motor fluctuations. Methods: In BIPARK-1 and BIPARK-2, participants recorded sleep/awake periods, "OFF"-time, and "ON"-time in 24-hour PD diaries. Sleep metrics included sleep duration, awakenings after sleep onset, and percent of sleep time spent awake. "OFF"-times included "OFF" before sleep (OBS), nighttime "OFF" (NTO), and early morning "OFF" (EMO). Data at baseline were pooled across treatment groups and analyzed descriptively. Mean values are presented with standard deviations (±SD). Results: Baseline data from 1010 participants were pooled for analysis. Among 964 participants with available sleep metrics, mean total sleep duration was 7.6 (±1.5) hours and longest duration of uninterrupted sleep was 7.2 (±1.9) hours. 332/964 (34.4%) participants experienced an "OFF"-episode before going to sleep and the mean duration of this OBS was 1.8±1.2 hours. 158/964 (16.4%) participants awoke after sleep onset; of these, 128/158 (81.0%) awoke in an "OFF"-state and the mean duration of this NTO was 1.0 (±0.5) hours. Among these 128 participants, the mean number of awakenings was 1.3 (±0.7) and percent of sleep time spent awake was 15.4% (±9.6%). 898/1005 (89.4%) participants experienced an "OFF"-episode upon waking up in the morning and the mean duration of this EMO was 1.5 (±0.9) hours. Conclusion: Results from this pooled analysis indicate that 34.4% of participants experienced an "OFF"-episode before going to sleep. Moreover, 81.0% of participants who woke up during the night were in an "OFF"-state upon awakening. Reducing "OFF"-episodes before and during the nighttime may help improve sleep in patients with PD, in turn potentially improving quality of life and daytime motor performance. Support (If Any): Neurocrine Biosciences, Inc.